The membrane glycoprotein M6a endocytic/recycling pathway involves clathrin-nediated endocytosis and affects neuronal synapses - García, Micaela D. (2017)
Fil: García, Micaela D. Universidad Nacional de San Martín. Instituto Tecnológico de Chascomús. Instituto de Investigaciones Biotecnológicas; Argentina